Radiation hardness study of the ePix100 sensor and ASIC under direct illumination at the European XFEL. (10th September 2021) - Klačková, I.; Ahmed, K.; Blaj, G.; Cascella, M.; Cerantola, V.; Chang, C.; Dragone, A.; Göde, S.; Hauf, S.; Kenney, C.; Segal, J.; Kuster, M.; et al.
Abstract: The ePix detector family provides multiple variants of hybrid pixel detectors to support a wide range of applications at free electron laser (FEL) facilities. The ePix detectors are by design versatile and easily re-configurable camera systems with common mechanical, electrical and data acquisition interfaces. Operation of detectors at FEL sources providing high brilliance, high repetition rate and ultra-short X-ray pulses poses a high risk of radiation damage to exposed detector components, such as the sensor and the readout Application Specific Integrated Circuit (ASIC). Knowledge about radiation-induced damage is important for understanding its influence on the quality of scientific data and the lifetime of the detector. We present the results of a systematic study of the influence of radiation-induced damage on the performance and lifetime of an ePix100a detector module using a direct attenuated beam of the European X-ray Free Electron Laser Facility (European XFEL) at 9 keV photon energy and average power of 10 μW. An area of 20 pixels×20 pixels was irradiated with an average photon flux of ≈ 7× 10 9 photons/s to a dose of approximately (760± 65) kGy at the location of the Si/SiO2 interfaces in the sensor. A dose dependent increase in both offset and noise of the ePix100a detector have been observed originating from an increase of the sensor leakage current. Moreover, we observed an effect directly after irradiation resulting in the saturation of individual pixels by their dark current. Changes in gain are evaluated one and half hours post-irradiation and suggest damage to occur also on the ASIC level. Based on the obtained results, thresholds for beam parameters are deduced and the detector lifetime is estimated with respect to the requirements to the data quality in order to satisfy the scientific standards defined by the experiments. We conclude the detector can withstand a beam with an energy up to 1 μJ at a photon energy of 9 keV impacting on an area of 1 mm 2 . The detector can be used without significant degradation of its performance for several years if the incident photon beam intensities do not exceed the detector's dynamic range by at least three orders of magnitude. Our results provide valuable input for the operation of the ePix100a detector at FEL facilities and the design of future detector technology.